A Wideband Feed Network for Vivaldi Antenna Arrays - Natasha Antoinette Hall; Johann Wilhelm Odendaal; Johan Joubert (International Journal of Antennas and Propagation)
A wideband feed network for a Vivaldi antenna array is presented. A limitation of current wideband antenna arrays is the bandwidth of either the feed network or the antenna element. The proposed antenna array consists of four wideband Vivaldi antennas fed with an improved wideband feed network to extend the useable bandwidth of the array. The proposed feed network consists of coplanar waveguide-to-slotline-to-microstrip line transitions. The feed network has a single coplanar waveguide input and four microstrip line output ports. The feed network achieved uniform amplitude and phase balance and an impedance bandwidth of 160% from 1 GHz to 9 GHz. The feed network was used in a uniform linear antenna array to feed four Vivaldi antenna elements. The Vivaldi antenna array achieved stable radiation patterns from 1.3 GHz to 8 GHz, resulting in a useable bandwidth of 144%. The antenna array has a minimum gain of 8 dBi and a maximum of 13.8 dBi within the frequency band. Results for a prototype Vivaldi antenna array, measured in a compact antenna test range, are presented and compared to simulated results from CST Studio Suite.